Low Voltage Delay Element with Dynamic Biasing Technique for Fully Integrated Cold-Start in Battery-Assistance DC Energy Harvesting Systems - Zushuai Xie; Zhiqiang Wu; Jianhui Wu (Applied Sciences, 2020)
This paper proposes an ultra-low voltage delay element for battery-assistance DC energy harvesting systems. By inserting a low voltage level shifter (VLS), a wider voltage range is obtained to bias the body of the delay element. Thus, both the voltage transfer curve (VTC) and the DC gain of the delay element are enhanced. Due to the introduction of the VLS, the cold start-up ring oscillator constituted by the proposed delay element can achieve oscillation under an extremely low input voltage. The fully integrated cold start-up ring oscillator with 21 stages of the proposed element is implemented in a standard 180 nm complementary metal oxide semiconductor (CMOS) process. The post-layout experimental results indicate that the cold start-up ring oscillator can retain oscillation when the power supply voltage (VDD) is 24 mV under a typical corner at room temperature. The output voltage swing of the cold start-up ring oscillator based on the proposed delay element is improved by more than 55% under VDD = 40 mV compared with a stacked inverter-based cold start-up ring oscillator. Monte Carlo (MC) simulation from 100 samples shows the enhanced output swing with the proposed delay element under process variation.